Brand Image Impact on Maritime Service Quality: Stakeholder Perspectives in Indonesian Shipping - Muhammad Dwi Arif; Akbar Prakoso; Pantjadjatmika; Syafril Zulmaidi; Octi Avriani (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
This research employs a qualitative approach to investigate how corporate brand image shapes the quality of maritime services, using a comprehensive stakeholder perspective within the Indonesian shipping industry. The study adopts PT. Multi Jaya Samudra’s TB. Maiden Central operations as its focal case, gathering insights from maritime professionals, academic experts, and industry practitioners to better understand the interconnection between brand perception and service delivery. Data were collected through semi-structured interviews with 65 participants, followed by a thematic analysis to identify emerging patterns. The results highlight that corporate brand image plays a substantial role in influencing how service quality is perceived, with a positive correlation of 79.8% found between brand strength and customer satisfaction. Key themes emerging from the analysis include the enhancement of professional trust, the incorporation of educational elements into industry practices, and the promotion of operational excellence. A robust and reputable brand is shown to provide shipping companies with a distinct competitive edge, while also aligning with broader objectives such as sustainable maritime growth and the adoption of digital innovation. Beyond practical business value, the research enriches the field of maritime business management by presenting a stakeholder-driven framework for brand development, offering opportunities for the integration of industry-relevant curricula in maritime vocational education, and promoting sustainable transportation practices. These findings yield actionable implications for Indonesian shipping enterprises that aim to strengthen brand positioning, improve service performance, and remain competitive in an increasingly dynamic and environmentally conscious maritime sector.